INVESTIGATING THE PRAGMATIC IMPLICATIONS OF MAXIM FLOUTING IN PETER PAN AND WENDY MOVIE DIALOGUE - Fatira, Hilayatul; Novitasari, Nine Febrie; Firdaus, Ahmad Yusuf (Universitas Bunda Mulia, 2025)
Peter Pan and Wendy (2023) is one of the many adaptations of the classic story Peter Pan and is considered a good example to study how people communicate in everyday situations. This research looks at how the characters in the movie flout conversational maxims, rules that people usually follow when they talk to each other. The research focuses on what types of maxim flouting happen in the movie and why the characters do it. To analyze this, the researcher used Grice’s theory (1975) to identify the types of maxims being flouted and Leech’s theory (1983) to find out the reasons behind them. The data were collected from the characters’ dialogues that show maxim flouting, and then analyzed using Spradley’s analytical procedures, namely domain analysis, taxonomic analysis, componential/contextual analysis, and cultural theme analysis. This study uses a descriptive qualitative method because it helps explain the meaning behind the characters’ utterances. The results indicate that there are thirty-one instances of maxim flouting in the movie, encompassing four types: manner, relevance, quantity, and quality. The most frequently flouted is the maxim of manner, while the least is quality. As for the reasons, the majority of the maxim flouting occurs due to collaborative purposes. In this context, the speaker intends to convey information or facilitate understanding without causing disruption or conflict in the interaction.